2022
DOI: 10.2147/nss.s369122
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Lower-Sodium Oxybate in an Open-Label Titration Period of a Phase 3 Clinical Study in Adults with Idiopathic Hypersomnia

Abstract: Purpose To report the efficacy and safety of lower-sodium oxybate (LXB; Xywav ® ) during the open-label titration and optimization period (OLT) and stable-dose period (SDP) in a clinical study for the treatment of idiopathic hypersomnia. Patients and Methods Data were collected during treatment titration and optimization in a phase 3 randomized withdrawal trial in adults (18–75 years of age) with idiopathic hypersomnia who took LXB treatment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The mean impairment scores on presenteeism (47.6%) and overall activity (64.0%) were lower than or similar to those observed in participants with idiopathic hypersomnia at baseline in a clinical trial (55.3% and 65.2%, respectively). 23 However, ARISE participants reported a mean absenteeism rate (12.3%) that was higher than that reported by participants in the idiopathic hypersomnia clinical trial (7.1%), 23 and even greater than that reported by people with narcolepsy in another clinical trial (6.1%). 31 Although ARISE participants’ absenteeism scores were highly variable, this rate is greatly concerning given that the absenteeism rate due to illness or injury in the overall US population is 1.3%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mean impairment scores on presenteeism (47.6%) and overall activity (64.0%) were lower than or similar to those observed in participants with idiopathic hypersomnia at baseline in a clinical trial (55.3% and 65.2%, respectively). 23 However, ARISE participants reported a mean absenteeism rate (12.3%) that was higher than that reported by participants in the idiopathic hypersomnia clinical trial (7.1%), 23 and even greater than that reported by people with narcolepsy in another clinical trial (6.1%). 31 Although ARISE participants’ absenteeism scores were highly variable, this rate is greatly concerning given that the absenteeism rate due to illness or injury in the overall US population is 1.3%.…”
Section: Discussionmentioning
confidence: 90%
“…The mean FOSQ-10 score of ARISE participants was similar to that of 154 participants in a clinical study at baseline (10.7 and 11.9, respectively), which is perhaps surprising given that 89.3% of ARISE participants were taking off-label medications for their idiopathic hypersomnia, compared with 55.8% of those from the clinical trial, and is suggestive of the inadequacy of available treatments, all of which were used off-label for idiopathic hypersomnia at the time of this study. 23 Multiple studies have shown that people with idiopathic hypersomnia are impaired on most, or all, health-related QoL domains of the SF-36 (role physical, role emotional, general health perception, vitality, social functioning, mental health, physical function, and bodily pain) compared with national norms, 12 , 24 , 25 even when the majority are treated with wake-promoting agents. 25 Individuals with idiopathic hypersomnia also report significantly worse health-related QoL than healthy controls on the EuroQoL 5-Dimension 5-Level index and the EuroQoL Visual Analog Scale.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 3, multicenter, placebo-controlled, double-blind, randomized withdrawal clinical trial (N = 154) evaluated the effect of this drug on IH symptoms. The primary effectiveness endpoint was the improvement in ESS score at the end of the trial, and as the secondary effectiveness endpoint, better outcomes on daytime functioning and work-activity impairment were observed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On other secondary and exploratory endpoints, LXB demonstrated improvement compared with placebo on the Clinical Global Impression of Change, functional outcomes, sleep inertia, work productivity, and activity impairment. In post hoc analyses, scores on several of these measures improved during open-label LXB treatment in the OLT and SDP 82 and were maintained long term over the 24-week OLE. 83 TEAEs were reported by 80% of participants overall and were consistent with those seen in the LXB study in narcolepsy.…”
Section: Introductionmentioning
confidence: 97%
“…LXB efficacy/tolerability is similar or superior to SXB for most patients with narcolepsy, although there are some patients who prefer SXB. 84 LXB is newly approved, and clinical trials of ~1 year in duration are available for narcolepsy and idiopathic hypersomnia; 52 , 53 , 76 , 82 for narcolepsy, there is also a well-established, 20-year history of SXB usage supporting certain benefits of oxybate treatment, including individualized optimization of dosing and regimen, improvement of QoL and functioning, and association with weight loss. LXB also has the benefit of reduced sodium content.…”
Section: Introductionmentioning
confidence: 99%